Challenges and Current Issues of Education in the Era of Digital and Technological Changes - Lesková, Andrea; Uličná, Zuzana; Tkáčová, Hedviga; Leka, Klodiana; Alvarez Mateo, Daniel (Journal of Education Culture and Society, 2023)
Aim. The aim of the article is to map out the current issues related to education in the era of digital and technological changes on the basis of theoretical and research findings. Methods. The published article is based on the theoretical and research findings of various authors and offers a critical reflection on some selected current aspects of education in the digital world, such as the problem of digital dementia and digital intelligence, the addiction associated with it, parenting styles, the development of critical thinking and the formation of a value system. Results. Creating an analysis that explores the current challenges of education in the digital age. Analysing the selected most frequent problems of the subject matter, primarily from the point of view of ethics, sociology, and psychology, based on several researches reflecting the risks of using modern technology and digital media. Conclusion. It is necessary to guide the child from early childhood to build values, critical thinking, but also own self-esteem and empathy. Since the foundations for a child’s education are laid in the family, it is precisely family education that can (un)prepare the child for entering the world of digital media and its optimal functioning in it. Cognitive value. The technologies that children and today’s young people use in their daily lives affect not only their physical, but especially their psychological health, self-esteem, and critical thinking. As such, it can be beneficial for further building and developing the theory and at the same time be a basis for additional research.